PENGARUH PELATIHAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN BANK SUMSEL BABEL - Nurul Mardiyyah Pratiwi; Fabio Mendes Soares; Destia Aktarina; Echi Kurniati (P3M STIE Mulia Darma Pratama, 2026)
This study aims to analyze the effect of training and compensation on employee performance at Bank Sumsel Babel Head Office, both partially and simultaneously. The research employed a quantitative approach using an associative research method. The population consisted of 133 permanent employees from the Business Division and the Operational and Service Division of Bank Sumsel Babel Head Office. A sample of 100 respondents was selected using the Slovin formula and proportionate stratified random sampling technique. Data were collected through questionnaires and literature studies. Multiple linear regression analysis with SPSS software was used to analyze the data. The results indicate that training has a positive and significant effect on employee performance, with a t-value of 4.184 greater than the t-table value of 1.985 and a significance level of 0.001 < 0.05. Compensation also has a positive and significant effect on employee performance, with a t-value of 7.118 greater than the t-table value of 1.985 and a significance level of 0.001 < 0.05. Simultaneously, training and compensation have a positive and significant effect on employee performance, as indicated by an F-value of 36.106 greater than the F-table value of 3.09 and a significance level of 0.001 < 0.05. The Adjusted R Square value of 0.415 indicates that training and compensation jointly explain 41.5% of the variation in employee performance, while the remaining 58.5% is influenced by other factors outside this study. Therefore, improving training quality and implementing a fair compensation system can enhance employee performance at Bank Sumsel Babel Head Office.